THE NEED FOR THE WORLD PEACE IN RIDLEY SCOTT’S KINGDOM OF HEAVEN MOVIE (2005): A SOCIOLOGICAL PERSPECTIVE - ASTUTI , FITRI YUNI (2010)
The research aims to show the need for the world peace in Kingdom Of Heaven movie by using a sociological perspective. It is done by establishing two objectives: the first is analyzing the film based on its structural elements and the second is analyzing the film based on sociological perspective.